Proposed new design and image of Fitness Leisure Centre for Rakan Muda Club Bukit Kiara, Kuala Lumpur / Nor’adawiah Soid - Soid, Nor’adawiah (Faculty of Architecture, Planning and Surveying, 2008)
Approchness of Kementerian Belia and Sukan to expand Rakan Muda Programme of Fitness Leisure Centre fox communities especially teenagers. This report is mainly regarding proposed new interior design scheme of Fitness Leisure Centre at Bangsar South The Village, Kerinchi Kuala Lumpur for Rakan Muda Club Bukit Kiara. The purposed is to build new centre for communities to do their leisury and fitness activities. The Aim is to attract the communities especially teenagers to come and exercise or leisurely visit at the Fitness Leisure Centre. The Research Methodology that have been used is regarding to the client’s need, questionnaire, internet, books, and the problems from current Fitness Centre. The case study also have been made at True Fitness, and Fitness First Wisma Spk Kl. From that case study, the disadvantages, advantages and facilities have been compared. The Fitness Leisure Centre was conceptualized as a Inspired by Nature and the image is modern look with nature elements. The concept is suitable to this project because the element of nature such as water feature, stone and pebbles, landscape and skylight will give the guests sense of freshness, nature, and relaxing mind that related to their health. The special of this project is all the activities and surrounding are not same concept and image with current Fitness Centre. It is because this project will give the guests new perspectives in experiencing the nature inspired surrounding and multi-facilities in Fitness Leisure Centre.